2014
DOI: 10.1111/arcm.12146
|View full text |Cite
|
Sign up to set email alerts
|

Early Renaissance Production Recipes for Naples Yellow Pigment: A Mineralogical and Lead Isotope Study of Italian Majolica from Montelupo (Florence)

Abstract: The Naples Yellow pigment was apparently used for the first time by the Egyptians, as a glass-colouring agent. Also known in the Mesopotamian and Roman cultures, the recipe was lost in Western Europe between the fourth and the 16th centuries AD. The recipe for the production of lead antimonate recently discovered in the 'Codice Calabranci' (second half of the 15th century) at Montelupo, a small town near Florence (Italy) known for its large-scale ceramic production, possibly represents the very first evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The two sets of majolica ceramics are different in typology and composition. It is interesting to compare their glaze microstructures and chemistries in an attempt to relate them to other analyses on tiles attributed to Pisano and on majolica objects, as well as on 50 Italian ceramic objects produced during the 14th‐16th centuries, as reviewed by Tite . Tite noted that double layer glazes were common in the 16th century, with 300‐600 μm thick glazes similar to those observed by Antonelli et al for nineteen 15th‐16th century ceramics.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…The two sets of majolica ceramics are different in typology and composition. It is interesting to compare their glaze microstructures and chemistries in an attempt to relate them to other analyses on tiles attributed to Pisano and on majolica objects, as well as on 50 Italian ceramic objects produced during the 14th‐16th centuries, as reviewed by Tite . Tite noted that double layer glazes were common in the 16th century, with 300‐600 μm thick glazes similar to those observed by Antonelli et al for nineteen 15th‐16th century ceramics.…”
Section: Discussionmentioning
confidence: 75%
“…The colors are obtained with the usual ions, Co in blue (0.4‐0.5 wt% CoO), Cu in green (2% CuO) and Fe in yellow (2 wt% Fe 2 O 3 ; up to 4 wt% in beige/honey/amber). In contrast to majolicas , no Sb was found in yellow glazes although its use has been known since the second millennium B.C . These characteristics are common to all the arista tiles studied by Coentro et al except that they found two green glazes containing Sn (2.5‐8.6 wt% SnO 2 ) in two arist a tiles from Seville belonging to the Instituto Valencia de Don Juan collection.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations